The Influence of Transformational Leadership and Job Satisfaction Towards Employee Engagement - Seno Djulian Saputra; Rima Rahmayanti (Green Publisher Indonesia, 2026)
The low employee engagement at PT BDP could potentially be influenced by aspects of job satisfaction that have not been fully met, as well as transformational leadership — one of the main antecedents of employee engagement. This leadership style provides psychological resources in the form of support, a sense of security, and a work environment that values individual contributions. This study aims to determine the effect of transformational leadership and job satisfaction, both partially and simultaneously, on employee engagement at PT Bumi Daya Plaza. The research method used quantitative associative analysis. The sampling technique used the Slovin technique with a sample size of 61 respondents. The research analysis used SPSS software with multiple linear regression analysis techniques, correlation tests, coefficient of determination tests, and partial and simultaneous hypothesis testing. The results indicate that transformational leadership and job satisfaction have a significant effect on employee engagement. Therefore, transformational leadership and job satisfaction that are unfavourable to employees will negatively affect employee engagement.